Hubungan Usia Ibu dengan Kejadian Anemia pada Kehamilan - Wijaya, Christian; Firmansyah, Yohanes; Santoso, alex (Pusat Riset dan Inovasi Nasional, 2025)
Pregnancy is a unique natural phenomenon but often causes complications due to anatomical and physiological changes that occur in the mother's body. One of the important health conditions to pay attention to in reducing maternal and perinatal mortality and morbidity is anemia in pregnancy. The prevalence of anemia during pregnancy is quite high, estimated at 38.2% worldwide, with the highest prevalence in Southeast Asia (48.7%). One of the factors that influence the incidence of anemia in pregnancy is maternal age. The aim of this research was to investigate whether there is a correlation between maternal age and the prevalence of anemia during pregnancy. This cross-sectional study was held at C Hospital from June to July 2019 by taking medical record data at the Midwifery Ward from January 2019 to December 2019. The variables of this study were the age of the mother recorded in the medical record when she gave birth at C-Hospital (chronological age) and the incidence of anemia as seen from the basic hematological results measured upon admission to the obstetric care room. Pearson Chi-Square test with Yates Correction was used for statistical analysis when the Expected Count was above 5% and Fisher's Exact Test when the Expected Count was below 5%. 924 respondents met the inclusion criteria. The chi-square statistical test results stated a significant relationship between maternal age and the incidence of anemia during pregnancy (p-value <0.001). In conclusion, maternal age has been shown to affect the incidence of anemia in pregnancy.